The Use of Topinambur (Jerusalem artichoke) Concentrate in the Curd Production - Chatinyan, N. R.; Minasyan, K. Zh.; Matevosyan, A. E.; Gevorgyan, S. H. (ՀԱԱՀ հիմնադրամ)
Curd production technology upon the use of topinambur (Jerusalem artichoke) tuber has been developed. For the curd production, hydrolyzed concentrate obtained from the tuber of Jerusalem artichoke has been used in the form of herbal supplement. New food product exceeds the traditional one in its biological values due to enrichment with carbohydrates, vitamins, nonessential and essential amino acids. The optimal dose of introducing the hydrolyzed concentrate has been also determined. The use of hydrolyzed concentrate of Jerusalem artichoke solution reduces the coagulation duration of milk mixture and increases the product yield; at the same time it saturates the product with inulin.
Keywords: Food Science and Technology